2019
DOI: 10.1093/nar/gkz557
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of specific DNA binding by the transcription factor ZBTB24

Abstract: ZBTB24, encoding a protein of the ZBTB family of transcriptional regulators, is one of four known genes—the other three being DNMT3B, CDCA7 and HELLS—that are mutated in immunodeficiency, centromeric instability and facial anomalies (ICF) syndrome, a genetic disorder characterized by DNA hypomethylation and antibody deficiency. The molecular mechanisms by which ZBTB24 regulates gene expression and the biological functions of ZBTB24 are poorly understood. Here, we identified a 12-bp consensus sequence [CT(G/T)C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 48 publications
2
44
0
Order By: Relevance
“…In the absence of a ChIP-seq suitable endogenous Zbtb24 antibody we used Ty1-tagged Zbtb24 to investigate genome-wide binding in mESCs (Figure 2A). Consistent with previous studies (Thompson et al 2018;Ren et al 2019), we found that most Zbtb24 peaks localized to promoters, exons and introns, and some overlapped with intergenic regions (Figure 2A; Table S2). The promoters of Cdca7, Ostc, Rnf187 and Cdc40 were among the strongest peaks (Table S2).…”
Section: Zbtb24 Occupancy and Sites Of Dna Methylation Gain Are Coupledsupporting
confidence: 91%
See 3 more Smart Citations
“…In the absence of a ChIP-seq suitable endogenous Zbtb24 antibody we used Ty1-tagged Zbtb24 to investigate genome-wide binding in mESCs (Figure 2A). Consistent with previous studies (Thompson et al 2018;Ren et al 2019), we found that most Zbtb24 peaks localized to promoters, exons and introns, and some overlapped with intergenic regions (Figure 2A; Table S2). The promoters of Cdca7, Ostc, Rnf187 and Cdc40 were among the strongest peaks (Table S2).…”
Section: Zbtb24 Occupancy and Sites Of Dna Methylation Gain Are Coupledsupporting
confidence: 91%
“…Intriguingly, promoters with aberrant DNA methylation gain included Zbtb24 targets previously identified in mESCs, such as Cdca7 and Arid5b Ren et al 2019) ( Table S1). We also confirmed ZBTB24-associated promoter hypermethylation by analysis of published Illumina 450K datasets from controls and ICF2 patients (Velasco et al 2018) ( Figure 1I; Figure S2), and again, some of these sites are known ZBTB24 targets in HCT116 cells (Thompson et al 2018).…”
Section: Wgbs and Rrbs Identify Hypo-and Hyper-dmrs In Zbtb24 Knock Omentioning
confidence: 95%
See 2 more Smart Citations
“…None of the reporter constructs were activated by EGFP–ZBTB24_ΔZFs. A 12‐bp ZBTB24 binding consensus motif [5′‐CT(G/T)NCAGGACCT‐3′] was recently identified by chromatin immunoprecipitation‐sequencing (ChIP‐seq) for both mouse and human ZBTB24 (Ren et al, ; Thompson et al, ). The two regions identified by the reporter assay, respectively, contained a 12‐bp sequence ( −225 CGCTCAGGACCG −214 and −48 CTTGCAGGACCT −37 ) showing complete or partial match with the consensus motif (Figure a).…”
Section: Resultsmentioning
confidence: 99%